2018
DOI: 10.3390/nu10091140
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Effects of Exercise on Appetite, Energy Intake, and Appetite-Related Hormones: The Modulating Effect of Adiposity, Sex, and Habitual Physical Activity

Abstract: Exercise facilitates weight control, partly through effects on appetite regulation. Single bouts of exercise induce a short-term energy deficit without stimulating compensatory effects on appetite, whilst limited evidence suggests that exercise training may modify subjective and homeostatic mediators of appetite in directions associated with enhanced meal-induced satiety. However, a large variability in responses exists between individuals. This article reviews the evidence relating to how adiposity, sex, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
117
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(135 citation statements)
references
References 124 publications
(299 reference statements)
11
117
0
7
Order By: Relevance
“…Habitual PA was measured with validated accelerometers that allow an estimation of the intensity and EE of habitual PA. Additionally, EE and EI (via DLW) and RMR (via indirect calorimetry) were measured with the gold‐standard methods to comprehensively assess all aspects of energy balance. The assessment of EI via validated laboratory‐based FI tests and via DLW over 2 weeks is a particularly major strength, as self‐reported EI, which is still commonly used in many trials today, has been found to be fundamentally inaccurate . A limitation of this analysis is that although PA assessment at follow‐up was performed while participants were still exercising at their prescribed dose, we did not measure habitual MVPA, steps per day, and PAEE continuously throughout the intervention period and thus have no record of the effect of the exercise training on these outcomes over the course of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Habitual PA was measured with validated accelerometers that allow an estimation of the intensity and EE of habitual PA. Additionally, EE and EI (via DLW) and RMR (via indirect calorimetry) were measured with the gold‐standard methods to comprehensively assess all aspects of energy balance. The assessment of EI via validated laboratory‐based FI tests and via DLW over 2 weeks is a particularly major strength, as self‐reported EI, which is still commonly used in many trials today, has been found to be fundamentally inaccurate . A limitation of this analysis is that although PA assessment at follow‐up was performed while participants were still exercising at their prescribed dose, we did not measure habitual MVPA, steps per day, and PAEE continuously throughout the intervention period and thus have no record of the effect of the exercise training on these outcomes over the course of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, for the sake of completeness, Hazell et al [32] did not find any change in overall energy nor macronutrients intake, after six weeks of sprint interval training in respect to pre-training. Furthermore, studies [38] focusing on the effect of physical exercise on appetite did not reach a definitive consensus: indeed, inconsistent results have been obtained regarding the effect of physical exercise in altering macronutrients and micronutrients intake. In this regard, it could be speculated that a major limitation of these studies contributing to the inconsistency of the results may reside in self-reported food diaries and questionnaires on food frequencies, together with short time data collection.…”
Section: Energy and Macronutrients Intakementioning
confidence: 99%
“…Based on data form Nakata et al, a significant increase in plasma nesfatin-1 in this condition may be one of the reasons for increasing insulin secretion and IR immediately after exercise. An increase nesfatin-1 after acute resistance exercise may be one of the mechanisms that can explain short-term anorexia after acute exercise which is reported by most studies (16,27). Data from control session showed a considerable decrease in nesfatin-1 in response to fasting condition.…”
Section: Discussionmentioning
confidence: 89%
“…Impact of physical activity and different types of exercise on the release of hormones involved in food intake and energy homeostasis showed the beneficial role of exercise and physical activity on appetite regulation (12). Exercise training in different modes can decrease adiposity and affect whole-body fat metabolism (13) This is an important aspect of exercise, whose main consequences are enhancing energy expenditure and release/suppression of hormones like orexigenic (NPY , ghrelin) and anorexigenic peptide/protein (obestatin, leptin, and visfatin) in central and peripheral tissues (14)(15)(16). Furthermore, some investigations suggest that appetite suppression in acute exercise is greatly intensity related and more intense exercises can cause greater stimulation of anorexigenic signals (14).…”
Section: Introductionmentioning
confidence: 99%